Fuzzy Logic Approach in Palm Oil Production Using the Mamdani Method - Bayu Adi Nugroho; Muhammad Faiz Assariy; Daffa Zulqisthi; Mrr.Lukie Trianawati; Sri Diana Sari; Nur Syahla Fatimah; Itsnaini Nur Rohmawati; Huwaida Asha Dhieva; Denisa Nurul Az Zahra; Arifa Fauzia Rahma; Chika Hayya Sabillah (Journal of Applied Science, Technology & Humanities | JASTH, 2025)
This research investigates the application of the Mamdani fuzzy logic method for predicting palm oil production based on consumer demand and supply data. The purpose is to enhance the accuracy of production forecasts critical for optimizing the palm oil industry in Indonesia. The methodology involves data collection on consumer demand and supply, formation of fuzzy sets, rule definition, and inference processing. Results indicate that the Mamdani method effectively correlates demand and supply levels with production outcomes, yielding consistent predictions when compared to manual calculations. The findings conclude that implementing fuzzy logic can significantly improve decision-making in palm oil production, leading to more efficient and sustainable practices within the industry. This study highlights the potential of fuzzy logic applications in agricultural production systems for better resource management.